THE EFFECT OF PINEAPPLE PEEL EXTACT IN DRINKING WATER ON THE PHYSICAL COMPOSITION OF JOPER CHICKEN CARCASS - R. R. P., Tondang; Ariana, I N. T.; Siti, N. W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of adding pineapple peel extract additives with different concentrations through drinking water on the physical composition of joper chicken carcasses aged 8 weeks. The research was conducted in the Sesetan lab, Denpasar for 6 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments, 5 replications, so the total experimental unit was 20. Each experimental unit used 3 joper chickens aged 2 weeks and a total of 60 joper chickens were used. The treatment given was P0: 0% pineapple peel extract, P1: 6% pineapple peel extract, P2: 8% pineapple peel extract and P3: 10% pineapple peel extract. The variables observed were carcass weight, carcass percentage, meat percentage, bone percentage and subcutaneous fat percentage including skin. The results of this study indicated that joper chickens fed pineapple peel extract as much as 6% - 10% had no significant difference (P>0.05) on carcass weight, carcass percentage, meat percentage, bone percentage and subcutaneous fat including skin percentage. Based on the results of this study it can be concluded that the addition of pineapple peel extract as much as 6% - 10% had no effect on carcass weight, carcass percentage, meat percentage, bone percentage and subcutaneous fat percentage including skin.